Development of an anaerobic capacity test for field sport athletes - Moore, A.; Murphy, A. (Journal of Science and Medicine in Sport, 2003)
Maximally accumulated oxygen deficit (MAOD) has been argued to be currently the best non-invasive method for estimating anaerobic capacity (Medbo et al., 1988, Ramsbottom et al., 1997). An easy to administer field test that could accurately predict MAOD, would be of great use to many field sport athletes and coaches. Fifteen male rugby union players undertook MAOD testing (99.4 +/- 16.9ml x kg(-1)) on a treadmill using a modification of procedure 3 as described by Medbo et al. (1988). All subjects also performed a 300m Shuttle Run Test (66.7 +/- 2.2s), run over a 20m distance. Analysis of the MAOD and 300m Shuttle Run Test time relationship revealed a significant correlation of r = -0.69 [p<0.01). Furthermore, a one-way analysis of variance (ANOVA) revealed that when subjects were split into 'good' and 'poor' groups based on 300m Shuttle Run Test times, the times distinguished between 'good' and 'poor' MAOD values (P<0.05). The findings of the present study support the validity of the 300m Shuttle Run Test as a useful estimate of anaerobic capacity in football athletes. Unexplained variance could be due to speed and agility factors associated with the 300m Shuttle Run Test. Methodological issues pertaining to the accurate assessment of MAOD are also discussed.